Long-term efficacy and safety of YAG laser vitreolysis for vision degrading myodesopsia - Tie-Zhu Lin; Cheng Shi; Xing Yang; Emmanuel Eric Pazo; Yan-Nian Hui; Li-Jun Shen (International Journal of Ophthalmology, 2023)
AIM: To assess the long-term efficacy and safety of yttrium-aluminum garnet (YAG) laser vitreolysis for vision degrading myodesopsia (VDM) caused by posterior vitreous detachment (PVD). METHODS: This retrospective study reviewed VDM patients of PVD type undergoing YAG laser vitreolysis. The baseline demographic information, the patterns of floaters, the number of floaters, and the subjective improvement of floater sympotoms (ranging from 0 to 100%) from medical records were collected. Significant improvement was defined as a relief of floater symptoms of ≥50% at the final visit. The long-term efficacy and safety of YAG laser vitreolysis were analyzed. The risk factors linked to significant improvement of floater symptoms were defined using univariate and multivariate logistic regression analyses. RESULTS: The final analysis included 221 patients with VDM. The mean age of patients was 61.08±7.74y, and the mean length of follow-up was 21.38±5.61mo. Totally 57.01% of patients experienced a significant improvement in their floater symptoms after YAG laser therapy, and none of them developed delayed retinal abnormalities such as retinal tears or detachments. Age (OR=1.049, 95%CI=1.007-1.092, P=0.021) was identified as a significant risk factor for significant improvement in VDM. CONCLUSION: YAG laser vitreolysis is an effective and secure treatment for PVD-type VDM, and patients of advanced age are more likely to get favorable outcomes.